Ruthenium oxide nano material doped with two or more than two p-region metals and / or transition metals, and preparation method and application thereof

The preparation of metal-doped ruthenium oxide nanomaterials was solved by the sol-gel method, and the problem of ruthenium dioxide structure and activity stability under high doping ratio was achieved, and an efficient acid oxygen evolution reaction was achieved.

CN119592979APending Publication Date: 2025-03-11SHENZHEN HINGEAR ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310984116.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the rutile phase crystal structure of rutile dioxide under high doping ratio, resulting in a decrease in activity and stability, and a lack of effective acidic oxygen evolution electrode materials.

Method used

Ruthenium oxide nanomaterials doped with two or more p-region metals and/or transition metals are prepared by sol-gel method to ensure that the doping ratio is between 1 and 50%, and metal agglomeration is prevented by multi-dentate ligand polymers to achieve uniform dispersion.

Benefits of technology

The rutile phase structure of rutile oxide under high doping ratio is achieved, which significantly improves the activity and stability of acidic oxygen evolution electrode materials, and can maintain long-term stability under high current density conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592979A_ABST
    Figure CN119592979A_ABST
Patent Text Reader

Abstract

The invention discloses a ruthenium oxide nano material doped with two or more than two p-region metals and / or transition metals. The molecular formula of the ruthenium oxide nano material is one of the following types: type I: two or more than two p-region metal doped ruthenium oxide nano materials P < 1 > x < 1 > P < 2 > x < 2 >... P < n > x < n > Ru < 1-x-x < 2 >...-x < n > O < 2 >; or the type II is as follows: two or more than two transition metal doped ruthenium oxide nano materials T < 1 > y < 1 > T < 2 > y < 2 >... T < n > y < n > Ru < 1-y < 1-y < 2 >...-y < n > O < 2 >; or a type 3: a ruthenium oxide nanomaterial P < 1 > x < 1 > P < 2 > x < 2 >... P < n > x < n > T < 1 > y < 1 > T < 2 > y < 2 >... T < n > y < n > Ru < 1-x-x-x-2 >...-x < n >-y < 1-y > 2...-y < n > O < 2 > co-doped with the p-region metal (P) and the transition metal (T); wherein P < 1 > x < 1 >, P < 2 > x < 2 >,..., P < n > x < n > are p-region metal, and the p-region metal is selected from one or more of gallium, indium, germanium, tin, lead, antimony and bismuth; t1y1, T2y2,..., Tnyn are transition metals, and the transition metals are selected from one or more of titanium, zirconium, hafnium, cadmium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, rhenium, iron, cobalt, nickel, copper, zinc, palladium, osmium, cerium and praseodymium. The invention also discloses a preparation method of the nano material and application of the nano material in an electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of inorganic advanced nanomaterials, and specifically relates to a ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals, a preparation method and use thereof. Background Art

[0002] With the consumption of traditional fossil energy, accompanied by the increasingly severe environmental pollution problems caused by its combustion, carbon dioxide emissions have increased, and the goals of "carbon peak" and "carbon neutrality" are still facing severe challenges. Therefore, it is imperative to develop new sustainable clean energy to replace fossil fuels. At present, solar energy, wind energy, bioenergy, tidal energy and hydrogen energy are relatively mature new alternative energy sources. Among them, hydrogen energy, as a clean energy, has high energy density, clean and pollution-free, and is increasingly receiving widespread attention. At the same time, there are many sources of hydrogen energy, including fossil fuel hydrogen production, carbon capture hydrogen production and water electrolysis hydrogen production. Among them, water electrolysis hydrogen production has a relatively simple process and a relatively mature technology among many production processes. Water electrolysis hydrogen production is divided into alkaline water electrolysis hydrogen production technology (ALK), solid oxide water electrolysis hydrogen production technology (SOEC) and proton exchange membrane water electrolysis technology (PEM). Compared with ALK technology, PEM hydrogen production has a higher working current density of PEM water electrolysis hydrogen production (>1A / cm 2 ), higher overall efficiency (74%~87%), higher hydrogen gas volume fraction (>99.99%), higher gas production pressure (3~4MPa), faster dynamic response speed, and can adapt to the volatility of renewable energy power generation. It is considered to be a water electrolysis hydrogen production technology with great development prospects.

[0003] However, the anode of the PEM electrolyzer has local super-strong acidity and oxidizing properties, which makes it difficult for general transition metal electrode materials such as iron, cobalt and nickel to dissolve quickly and work stably. Iridium oxide is currently a commercial catalyst for PEM due to its extremely high acidic oxygen evolution stability. However, its soaring price and scarce resources make it difficult to use it on a large scale and it is difficult to meet the future demand for hydrogen energy. With the successful preparation of domestic proton exchange membranes, the cost of membranes will drop significantly in the future. Seeking alternative active and stable acidic oxygen evolution electrode materials is the key to reducing the cost of pure water electrolysis.

[0004] Ruthenium oxide has a very high acidic oxygen evolution activity, but its potential of 1.33V (relative to the standard hydrogen electrode) when oxidized to RuO4 is within the working potential of the oxygen evolution reaction, so that the oxygen evolution process is accompanied by the oxidation of ruthenium, which eventually causes the generation of high-valent ruthenium oxides and dissolution in the electrolyte, ultimately leading to the loss of active sites and the attenuation of the catalytic oxygen evolution reaction performance. However, its low price makes the design of highly active and highly stable ruthenium-based oxygen evolution catalysts very promising and challenging.

[0005] In recent years, researchers have made a lot of efforts to improve the oxygen evolution activity and stability of ruthenium-based catalysts. For example, transition metals such as manganese, iron, cobalt, nickel, chromium and zinc are used to dope ruthenium oxide, defects are introduced into ruthenium oxide, the morphology of ruthenium oxide is regulated, and ruthenium oxide is loaded on a stable substrate, etc., ultimately achieving a change in the electronic structure of ruthenium oxide, improving its adsorption with oxygen-containing intermediates, and further improving the electrocatalytic oxygen evolution performance and stability. However, the problem of low activity and poor stability has not yet been solved. Among them, in some of the works that use metal elements to dope ruthenium oxide to regulate its performance, since ruthenium is also a precious metal, reducing its material consumption, but still maintaining its activity and stability is also the focus of designing electrocatalytic oxygen evolution materials. However, in recent years, the content of other non-precious metal elements often introduced by scientific researchers is very low, and there is almost no metal doping amount greater than 20% and above. The reason is that after reviewing the technical literature of predecessors, people found that when the doping ratio [i.e., doping metal / (doping metal+Ru), molar ratio] is greater than 10%, the rutile phase crystal structure of ruthenium dioxide will be changed after doping, such as the generation of various non-rutile phase impurity crystals, which are difficult to separate from the rutile phase and have various negative effects on the electrolysis of water. When the doping ratio is greater than 15% or even higher than 20%, the rutile phase crystal structure of ruthenium dioxide will be significantly destroyed, resulting in the large-scale generation of various impurities. Therefore, people usually dare not expect the doping ratio to be higher than 20%. Moreover, for ruthenium dioxide with a high metal doping amount, due to the reduction of ruthenium content, that is, the reduction of active sites, its activity tends to decrease rapidly, and the stability also decreases accordingly, and the existing problem of improving the performance and stability of electrocatalytic oxygen evolution cannot be solved at the same time. In addition, few scientific researchers like to use the method of combining multiple metals. Because they often have these wrong perceptions: they believe that various elements are mutually different and produce repulsion, or that the radius of the metal elements does not match, the electronegativity is different, the redox activity is not suitable, and the doping conditions are different. As a result, multiple metal elements with large differences cannot enter the ruthenium dioxide lattice at the same time, but instead destroy the crystal structure of ruthenium dioxide, resulting in the counterproductive consequence that both the activity and stability of ruthenium dioxide are deteriorating.

[0006] In order to solve the above problems, the present invention is proposed. Summary of the invention

[0007] The present invention adopts a sol-gel method to prepare a ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals, which exhibits ultra-high activity and stability when used as an acidic oxygen evolution electrode material.

[0008] The ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals disclosed in the present invention has a molecular formula of one of the following three types:

[0009] Type 1: Ruthenium oxide nanomaterials doped with two or more p-zone metals 1 x1 P 2 x2...... P n xn Ru 1-x1-x2-......-xn O2; or

[0010] Type 2: Ruthenium oxide nanomaterials doped with two or more transition metals 1 y1 T 2 y2...... T n yn Ru 1-y1-y2-......-yn O2; or

[0011] Type 3: Ruthenium oxide nanomaterials co-doped with p-zone metal (P) and transition metal (T) 1 x1 P 2 x2...... P n xn T 1 y1 T 2 y2...... T n yn Ru 1-x1-x2-......-xn-y1-y2-......-yn O2;

[0012] Among them, P 1 x1 , P 2 x2 ,......P n xn is a p-zone metal, wherein the p-zone metal is selected from one or more of gallium, indium, germanium, tin, lead, antimony, and bismuth; T 1 y1 , T 2 y2 ,......T n yn The transition metal is selected from one or more of titanium, zirconium, hafnium, cadmium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, rhenium, iron, cobalt, nickel, copper, zinc, palladium, osmium, cerium and praseodymium.

[0013] In the present invention, the total doping ratio, i.e. the molar ratio of the doped metal to the total metal (including Ru), is 1-50%, i.e. x1+x2+......+x n +y1+y2+......y n =1~50%, but the molar ratio between each doping metal is not limited.

[0014] In the present invention, the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals still maintains the crystal structure of rutile phase ruthenium oxide after doping.

[0015] Preferably, the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals is a nanoparticle with a rough and porous surface. Preferably, the nanoparticle has a size of 5 to 200 nm, more preferably 50 to 100 nm.

[0016] Preferably, the p-zone metal and / or transition metal and ruthenium are uniformly dispersed in the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals. In other words, the doped metal is uniformly dispersed in the nanomaterial in an atomic-level dispersion manner.

[0017] The rutile phase ruthenium oxide crystal has a 101 crystal plane and a 110 crystal plane. The spacing between the 101 crystal planes of the undoped rutile phase ruthenium oxide is 0.254nm, and the spacing between the 110 crystal planes is 0.315nm. From the perspective of lattice spacing, the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals of the present invention will have different degrees of widening or narrowing compared to the lattice spacing of the undoped rutile phase ruthenium oxide material, which has a great relationship with the doping elements, and thus more advantageously proves that the p-zone metal and / or transition metal combination is indeed doped into the interior of the ruthenium oxide lattice, and the p-zone metal and / or transition metal do replace the position of ruthenium in part of the lattice, but the overall nanomaterial still maintains the crystal structure of the rutile phase ruthenium oxide after doping.

[0018] The second aspect of the present invention provides a method for preparing the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals as described in the first aspect, wherein the preparation method is a sol-gel method, comprising the following steps:

[0019] Step (1), placing the complex into a solution containing a ruthenium source and two or more p-block metal sources and / or transition metal sources to obtain a mixture, sealing the mixture in a container, mixing and stirring for several hours, opening the container lid, evaporating the solvent such as by evaporation or freeze drying, scraping out the powder, and obtaining a metal complex precursor;

[0020] Step (2), heating the metal complex precursor obtained in step (1) to a desired temperature, keeping it at that temperature for several hours, cooling it naturally and taking it out to obtain a powder, that is, the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals.

[0021] Preferably, the p-zone metal source and / or transition metal source is selected from: chlorides of p-zone metals and / or transition metals, organic esters of p-zone metals and / or transition metals, carbonyl compounds of p-zone metals and / or transition metals, oxalates of p-zone metals and / or transition metals, nitrates of p-zone metals and / or transition metals, ammonium oxalates of p-zone metals and / or transition metals, and low-valent or high-valent acid salts of p-zone metals and / or transition metals.

[0022] Preferably, the ruthenium source is one or more of ruthenium chloride, ruthenium carbonyl, ruthenium acetylacetonate or ruthenium nitrosyl nitrate;

[0023] Preferably, the complex is a polymer containing multiple coordination points. More preferably, the polymer containing multiple coordination points is selected from one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, polyethylene diamine, polylactic acid, polypyridine, citric acid, ethylenediaminetetraacetic acid and polyamide.

[0024] The solution of the p-zone metal source, transition metal source and ruthenium source may be an aqueous solution or an alcohol solution, as long as the p-zone metal source and / or transition metal source and ruthenium source can be dissolved.

[0025] Preferably, in the mixture of step (1), the concentration of the p-zone metal source and / or transition metal source is 0.01-1 mol / L; the concentration of the ruthenium source is 0.1-1 mol / L; and the concentration of the complex is 1-40 g / L.

[0026] Preferably, in step (1), the sealing mixing temperature is 70 to 150 degrees Celsius and the time is 10 to 15 hours.

[0027] Preferably, the heating rate in step (2) is 1-10° C. / min, the required temperature is 400-600° C., and the insulation time is 3-6 hours.

[0028] Preferably, the molar ratio of ruthenium to all doping metals is 99:1 to 1:1.

[0029] The third aspect of the present invention provides the use of the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals as described in the first aspect as an electrode material.

[0030] Preferably, the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals is used as an anode material for oxygen evolution in acidic water electrolysis.

[0031] The above technical solutions can be freely combined under the premise of no contradiction.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals of the present invention is reported for the first time, and achieves the unexpected effect of multi-metal element combination doping and high doping ratio while still maintaining the rutile crystal form of RuO2. In the present invention, the p-zone metals and / or transition metals have no mutually exclusive effect, and can be combined and doped into the ruthenium oxide lattice. Although the radius of some metal ions is much larger than that of ruthenium ions, the p-zone metals and / or transition metals can still replace the position of ruthenium in part of the lattice, thereby maintaining the crystal structure of rutile phase ruthenium oxide. Moreover, the doping ratio in the present invention can be as high as 50%, and the intrinsic structure of ruthenium oxide is still not destroyed, and the crystal structure of rutile phase ruthenium oxide is still perfectly maintained. In contrast, the metal doping amount of ruthenium dioxide doped with metal elements reported in the prior art is very low, almost no more than 15%, and the increase in doping amount will also change the crystal structure of ruthenium dioxide, and even greatly reduce the activity and stability of ruthenium dioxide. In addition, a variety of p-block metals and / or transition metals are highly evenly dispersed in the material, without the generation of impure p-block metal and / or transition metal oxides and ruthenium alone, so that the active site ruthenium is well regulated and remains stable during the oxygen evolution reaction.

[0034] 2. The ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals of the present invention has uniform particle size, is porous, and has a simple synthesis method. Since the doping amount of the metal element is increased, the amount of the precious metal ruthenium is further reduced. After the doping of two or more p-zone metals and / or transition metals, due to the introduction of a combination of multiple p-zone metals and / or transition metals with different characteristics and advantages, they coordinate with each other, and the electronic structure is redistributed, resulting in a weakening of the covalency of the ruthenium oxygen bond, so that the active site ruthenium is in a lower valence state. The use of the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals for acidic water electrolysis oxygen evolution anode materials shows extremely high activity and stability. In the stability test process of the acidic electrolyte, the nanomaterial of the present invention does not dissolve and has a certain stability. When it is under the working condition of high current density, the constant current stability curve can remain stable for a long time.

[0035] 3. Without being limited to any technical theory, the inventors of the present invention believe that when transition metal elements such as manganese, chromium, molybdenum, tungsten, and vanadium are used, they will be fully oxidized and dispersed in ruthenium dioxide in a stable form due to being in a high temperature and high pressure environment or using their high-valent metal salts for reaction during synthesis, so that the ruthenium active sites can be stably regulated during the acidic oxygen evolution process, so that the stability of ruthenium oxide is improved. In addition, the doping of transition metal elements such as manganese, chromium, molybdenum, tungsten, and vanadium can adjust the d-band center of the ruthenium active site, reduce the surface-adsorbate state of the antibonding, thereby reducing the free energy of the rate-determining step, and ultimately improving the intrinsic activity of ruthenium oxide. In addition, the combination of p-zone metals and / or transition metals with different electronic structures and electronegativity, or the co-doping of p-zone metals and / or transition metals with different valence states and different redox activities, due to the synergistic effect between the metals, each of which has its own division of labor, leads to electron redistribution, regulates the electronic structure of ruthenium oxide, and inhibits the excessive oxidation of Ru to volatile RuO4 or soluble RuO5 at high potential (>1.4V). 2- , and reduces the adsorption energy of oxygen intermediates, thereby improving the activity and stability of ruthenium oxide. However, the iron, cobalt, nickel, chromium and zinc elements commonly doped in ruthenium oxide do not have the above effects. The doping of iron, cobalt, nickel, chromium and zinc is usually because their lower valence states are not compatible with the tetravalent ruthenium oxide, resulting in oxygen defects, and ultimately changing its oxygen evolution reaction mechanism to a lattice oxygen oxidation mechanism, and ultimately improving its oxygen evolution reaction activity. However, the instability of oxygen defects makes it impossible to maintain the stability of the catalyst, so that activity and stability cannot be taken into account. The present invention can regulate ruthenium oxide crystals from multiple angles, taking into account improving the activity and stability of ruthenium dioxide;

[0036] 4. In terms of activity: When the nanomaterial of the present invention is used as an anode material for oxygen evolution in acidic water electrolysis, when the total p-zone metal and / or transition metal doping amount is 1at% to 50at% (at% is the metal molar fraction, based on the total molar amount of metal in the ruthenium oxide nanomaterial doped with the p-zone metal and / or transition metal combination as a benchmark), the intrinsic activity is relatively high. Specifically, it can be seen from Tables 1-3 below that the p-zone metal and / or transition metal combination doped ruthenium oxide nanomaterial obtained in the embodiment has good water electrolysis oxygen evolution performance, and the overpotential at a current density of 10 mA per square centimeter is mostly lower than 346 mV of commercial ruthenium dioxide.

[0037] 5. In terms of stability: When the ruthenium oxide nanomaterial doped with a combination of p-zone metals and / or transition metals of the present invention is used as an anode material for oxygen evolution in acidic water electrolysis, it has a high stability at high current densities of 100 and 200 mA cm -2Under working conditions, the constant current stability curve can still maintain a relatively high stability time, proving that the ruthenium oxide nanomaterials doped with a combination of p-region metals and / or transition metals have excellent acidic oxygen evolution reaction stability. In addition, when the ruthenium oxide nanomaterials doped with a combination of p-region metals and / or transition metals are used as anode materials for oxygen evolution in water electrolysis, the PEM device stability measured at 80°C is excellent, which also proves that the ruthenium oxide nanomaterials doped with a combination of p-region metals and / or transition metals have excellent acidic oxygen evolution reaction stability.

[0038] 6. The preparation method of the present invention is a sol-gel method. The sol-gel method is a method of synthesis under simple sol-gel reaction combined with air calcination. The method is simple, low-cost, reproducible, environmentally friendly, and can be scaled up for preparation, which is suitable for industrial promotion. The preparation method described in the present invention is simple and provides a new idea for synthesizing highly active electrode materials.

[0039] 7. In the sol-gel method of the present invention, the multi-dentate ligand polymer is used to form a complex with the metal cation. Compared with small molecule complexes, the polymer multi-dentate ligand prevents the metals from agglomerating and forming a heterogeneous phase, which is conducive to the uniform dispersion of high-concentration multiple different metals in the final product, and can improve the activity and stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a scanning electron microscope schematic (SEM) diagram of the gallium-indium bimetallic element doped ruthenium dioxide nanomaterial in Example 1;

[0041] Figure 2 This is the X-ray diffraction pattern (XRD) of the ruthenium dioxide nanomaterial doped with gallium and indium bimetallic elements in Example 1;

[0042] Figure 3 This is a scanning electron microscope schematic (SEM) diagram of the gallium-tin bimetallic element doped ruthenium dioxide nanomaterial in Example 2;

[0043] Figure 4 This is the X-ray diffraction pattern (XRD) of the gallium-tin bimetallic element doped ruthenium dioxide nanomaterial of Example 2;

[0044] Figure 5 Transmission electron microscopy (TEM) of gallium-bismuth bimetallic elements doped ruthenium dioxide nanomaterials in Example 3;

[0045] Figure 6 The X-ray diffraction pattern (XRD) of the ruthenium dioxide nanomaterial doped with the tin-indium bimetallic elements in Example 4;

[0046] Figure 7 This is a high-resolution electron microscopy image (HRTEM) of the tin-bismuth bimetallic element-doped ruthenium dioxide nanomaterial of Example 5;

[0047] Figure 8 This is the X-ray diffraction pattern (XRD) of the ruthenium dioxide nanomaterial doped with indium and bismuth bimetallic elements in Example 6;

[0048] Fig. 9 This is the X-ray diffraction pattern (XRD) of the titanium-niobium bimetallic element-doped ruthenium dioxide nanomaterial of Example 7;

[0049] Fig.10 This is a schematic diagram of a scanning electron microscope (SEM) of the titanium-tantalum bimetallic element doped ruthenium dioxide nanomaterial in Example 8;

[0050] Fig.11 This is a schematic diagram of a scanning electron microscope (SEM) of the titanium-manganese bimetallic element doped ruthenium dioxide nanomaterial in Example 9;

[0051] Fig.12 This is the X-ray diffraction pattern (XRD) of the titanium-platinum bimetallic element doped ruthenium dioxide nanomaterial of Example 10;

[0052] Fig.13 This is a scanning electron microscope schematic (SEM) diagram of the titanium-palladium bimetallic element doped ruthenium dioxide nanomaterial in Example 11;

[0053] Fig.14 This is the X-ray diffraction pattern (XRD) of the titanium-cobalt bimetallic element doped ruthenium dioxide nanomaterial of Example 12;

[0054] Fig.15 This is a scanning electron microscope schematic (SEM) diagram of the niobium and tantalum bimetallic elements doped ruthenium dioxide nanomaterials of Example 13;

[0055] Fig.16 This is the element distribution diagram of the niobium and manganese bimetallic elements doped ruthenium dioxide nanomaterial in Example 14;

[0056] Fig.17 This is the X-ray diffraction pattern (XRD) of the niobium and manganese bimetallic elements doped ruthenium dioxide nanomaterial in Example 14;

[0057] Fig.18 This is the X-ray diffraction pattern (XRD) of the niobium-chromium bimetallic element doped ruthenium dioxide nanomaterial in Example 15;

[0058] Fig.19 This is a scanning electron microscope schematic (SEM) diagram of the niobium-palladium bimetallic element doped ruthenium dioxide nanomaterial in Example 16;

[0059] Fig. 20 This is the X-ray diffraction pattern (XRD) of the niobium and cobalt bimetallic elements doped ruthenium dioxide nanomaterial of Example 17;

[0060] Fig.21This is a scanning electron microscope schematic (SEM) diagram of the tantalum-manganese bimetallic element doped ruthenium dioxide nanomaterial in Example 18;

[0061] Fig. 22 This is a scanning electron microscope schematic (SEM) diagram of the tantalum-platinum bimetallic element-doped ruthenium dioxide nanomaterial of Example 19;

[0062] Fig.23 This is the X-ray diffraction pattern (XRD) of the ruthenium dioxide nanomaterial doped with tantalum-chromium bimetallic elements in Example 20;

[0063] Fig.24 The X-ray diffraction pattern (XRD) of the tantalum-cobalt bimetallic element-doped ruthenium dioxide nanomaterial of Example 21;

[0064] Fig.25 This is the X-ray diffraction pattern (XRD) of the niobium, manganese, cobalt and tantalum multi-metal element doped ruthenium dioxide nanomaterial of Example 22;

[0065] Fig.26 This is the element distribution diagram of niobium, manganese, cobalt and tantalum multi-metal elements doped with ruthenium dioxide in Example 22;

[0066] Fig. 27 This is the X-ray diffraction pattern (XRD) of the niobium, manganese, vanadium, gallium multi-metal element doped ruthenium dioxide nanomaterial of Example 23;

[0067] Fig.28 This is the element distribution diagram of niobium, manganese, vanadium, gallium multi-metal element doped ruthenium dioxide in Example 23;

[0068] Fig.29 This is a schematic diagram of a scanning electron microscope (SEM) of the gallium-chromium bimetallic element doped ruthenium dioxide nanomaterial of Example 24;

[0069] Fig.30 This is a scanning electron microscope schematic (SEM) diagram of the gallium-titanium bimetallic element doped ruthenium dioxide nanomaterial of Example 25;

[0070] Fig.31 This is the X-ray diffraction pattern (XRD) of the gallium-manganese bimetallic element doped ruthenium dioxide nanomaterial of Example 26;

[0071] Fig.32 This is a scanning electron microscope schematic (SEM) diagram of the ruthenium dioxide nanomaterial doped with tin-chromium bimetallic elements in Example 27;

[0072] Fig.33 This is the X-ray diffraction pattern (XRD) of the tin-niobium bimetallic element doped ruthenium dioxide nanomaterial of Example 28;

[0073] Fig.34 The X-ray diffraction pattern (XRD) of the ruthenium dioxide nanomaterial doped with the tin-tantalum bimetallic elements in Example 29;

[0074] Fig.35 This is a scanning electron microscope schematic (SEM) diagram of the ruthenium dioxide nanomaterial doped with tin-cobalt bimetallic elements in Example 30;

[0075] Fig.36 Polarization curves of oxygen evolution reaction in 0.5 mol / L H2SO4 solution using Examples 1, 3, 6 and commercial ruthenium dioxide as oxygen evolution anode materials.

[0076] Fig.37 The stability curves of the oxygen evolution reaction in 0.5 mol / L H2SO4 solution using Examples 1, 3, 6 and commercial ruthenium dioxide as oxygen evolution anode materials.

[0077] Fig.38 The polarization curves of the oxygen evolution reaction of Examples 8, 14 and 17 as oxygen evolution anode materials in 0.5 mol / L H2SO4 solution.

[0078] Fig.39 The stability curves of the oxygen evolution reaction of Examples 8, 14 and 17 as oxygen evolution anode materials in 0.5 mol / L H2SO4 solution.

[0079] Fig.40 The polarization curves of the oxygen evolution reaction of Examples 23, 27 and 28 as oxygen evolution anode materials in 0.5 mol / L H2SO4 solution.

[0080] Fig.41 The stability curve diagram of the oxygen evolution reaction of Examples 23, 27 and 28 as oxygen evolution anode materials in 0.5 mol / L H2SO4 solution.

[0081] Fig.42 This is the stability curve of the PEM device measured at 80°C using niobium and manganese bimetallic doped ruthenium dioxide and commercial ruthenium dioxide as oxygen evolution anode materials in Example 14. DETAILED DESCRIPTION

[0082] The present invention is further described below by way of examples, but is not limited to the examples. The experimental methods in the examples without specifying specific conditions are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified. The raw materials required in the following examples and comparative examples are all commercially available.

[0083] In the following experiments, a three-electrode system was used to test the electrolytic water oxygen evolution activity of the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals of the present invention to obtain a polarization curve. Three-electrode system: the reference electrode is a silver-silver chloride electrode, the counter electrode is a platinum sheet electrode, and the working electrode is a ruthenium oxide nanomaterial doped with a combination of two or more p-zone metals and / or transition metals obtained in the embodiment. When comparison is required, the working electrode uses other materials specified below as comparison.

[0084] In the following experiments, a two-electrode system was used to test the electrolytic water oxygen evolution stability of the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals of the present invention, and a stability curve was obtained. Two-electrode system: the cathode is a platinum sheet electrode, and the anode is a ruthenium oxide nanomaterial doped with a combination of two or more p-zone metals and / or transition metals obtained in the embodiment. When comparison is required, the working electrode uses other materials specified below as comparison.

[0085] The specific embodiments are as follows:

[0086] Example 1-GaIn bimetallic elements doped with ruthenium dioxide

[0087] (1) Prepare gallium chloride ethanol solution, indium chloride ethanol solution and ruthenium chloride ethanol solution of 15 mg / mL respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride in the reactor to 0.1 mol / L, gallium chloride concentration to 0.0025 mol / L, and indium chloride concentration to 0.0225 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0088] Then, polyvinyl pyrrolidone powder of a multidentate ligand polymer was added to the solution (the concentration of polyvinyl pyrrolidone in the complex was controlled to be 40 g / L), and the mixture was sealed and ultrasonicated for several hours to obtain a mixed solution with uniform color. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 70°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a metal powder precursor with uniform color.

[0089] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample. Wash it with deionized water and ethanol several times and dry it to obtain the gallium-indium dual-doped ruthenium oxide nanomaterial, wherein the gallium doping amount is calculated as follows: n(Ga%) = N Ga / (N Ga+N In +N Ru )*100%=1%. The calculation formula of indium doping amount is: n(In%)=N In / (N Ga +N In +N Ru )*100%=9%.

[0090] Characterization of GaIn bimetallic doped ruthenium oxide materials:

[0091] The scanning electron microscope image of the obtained gallium-indium bimetallic doped ruthenium oxide material is shown in the attached Figure 1 The XRD spectrum is shown in the attached Figure 2 .from Figure 1 It can be seen that the particle size of the gallium-indium dual-doped ruthenium dioxide nanomaterial is small, between 50-200nm, and is very uniform with a rough and porous surface.

[0092] The XRD spectrum of the obtained gallium-indium bimetallic doped ruthenium oxide nanomaterial is shown in the attached Figure 2 .from Figure 2 It can be seen that the gallium-indium dual-doped ruthenium oxide nanomaterial exhibits the characteristic peaks of rutile phase ruthenium oxide. And there are no diffraction peaks of any other oxides, indicating that gallium and indium are successfully doped into the lattice of ruthenium oxide without phase separation. That is, gallium and indium in the gallium-indium dual-metal doped ruthenium oxide nanomaterial are doped into the lattice of ruthenium oxide to replace the position of ruthenium in part of the lattice.

[0093] therefore, Figure 2 Prove that the molecular formula of the material is Ga x In y Ru 1-x-y O2.

[0094] Example 2-GaSn bimetallic elements doped with ruthenium dioxide

[0095] (1) Prepare gallium nitrate ethanol solution, tin chloride ethanol solution and ruthenium chloride ethanol solution of 15 mg / mL respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride in the reactor to 0.1 mol / L, gallium nitrate concentration to 0.0225 mol / L, and tin chloride concentration to 0.0025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0096] Then, add the multidentate ligand polymer polypyridine powder to the solution (control the polypyridine concentration of the complex to be 30g / L), continue to seal and ultrasonicate for several hours to obtain a mixed solution with uniform color. Then, put the glass reactor into a constant temperature oil bath pot and keep it at a constant temperature of 60℃ for 14 hours. Then, open the lid and evaporate the solvent to obtain a metal powder precursor with uniform color.

[0097] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the gallium-tin bimetallic element doped ruthenium oxide nanomaterial, wherein the gallium doping amount is calculated as follows: n(Ga%) = N Ga / (N Ga +N Sn +N Ru )*100%=9%. The calculation formula of tin doping amount is: n(Sn%)=N Sn / (N Ga +N Sn +N Ru )*100%=1%.

[0098] Characterization of GaSn bimetallic doped ruthenium oxide materials:

[0099] The scanning electron microscope image of the obtained gallium-tin bimetallic doped ruthenium oxide material is shown in the attached Figure 3 The XRD spectrum is shown in the attached Figure 4 .from Figure 3 It can be seen that the particles of gallium-tin bimetallic doped ruthenium dioxide nanomaterials are small in size and evenly distributed.

[0100] The XRD spectrum of the obtained gallium-tin bimetallic doped ruthenium oxide nanomaterial is shown in the attached Figure 4 .from Figure 4 It can be seen that the gallium-tin dual-doped ruthenium oxide nanomaterial exhibits the characteristic peaks of rutile phase ruthenium oxide. And there are no diffraction peaks of any other oxides, indicating that gallium and tin are successfully doped into the lattice of ruthenium oxide, and no phase separation occurs. That is, gallium and tin in the gallium-tin dual-metal doped ruthenium oxide nanomaterial are doped into the lattice of ruthenium oxide to replace the position of ruthenium in part of the lattice.

[0101] Example 3-Ga-Bi bimetallic elements doped with ruthenium dioxide

[0102] (1) Prepare gallium nitrate aqueous solution, bismuth chloride hydrochloric acid aqueous solution and 15 mg / mL nitrosyl ruthenium nitrate aqueous solution respectively, and add the corresponding solution volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element, control the concentration of nitrosyl ruthenium nitrate aqueous solution in the reactor to be 0.245 mol / L, gallium nitrate concentration to be 0.0025 mol / L, and bismuth chloride concentration to be 0.0025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0103] Then, add the multidentate ligand polymer polyethylenediamine to the solution, continue to seal and ultrasonicate for several hours to obtain a mixed solution with uniform color. Then, put the glass reactor into a constant temperature oil bath pot and keep it at 80℃ for 10 hours. Then, open the lid and evaporate the solvent to obtain a metal powder precursor with uniform color.

[0104] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the gallium-bismuth bimetallic element doped ruthenium oxide nanomaterial, wherein the gallium doping amount is calculated as follows: n(Ga%) = N Ga / (N Ga +N Bi +N Ru )*100%=1%. The calculation formula of tin doping amount is: n(Bi%)=N Bi / (N Bi +N Ga +N Ru )*100%=1%.

[0105] Characterization of gallium-bismuth bimetallic doped ruthenium oxide materials:

[0106] The transmission electron microscopy of the obtained gallium-bismuth bimetallic doped ruthenium oxide material is shown in the attached Figure 5 ,from Figure 5 It can be seen that the particles of gallium-bismuth bimetallic doped ruthenium dioxide nanomaterials are small in size and evenly distributed.

[0107] Example 4 - Tin-Indium Bimetallic Elements Doped Ruthenium Dioxide

[0108] (1) Prepare 15 mg / mL of stannous chloride ethanol solution, indium chloride ethanol solution and ruthenium chloride ethanol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride in the reactor to be 0.175 mol / L, the concentration of stannous chloride to be 0.05 mol / L, and the concentration of indium chloride to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0109] Then, add the multidentate ligand polymer polylactic acid to the solution, continue to seal and ultrasonicate for several hours to obtain a mixed solution with uniform color. Then, put the glass reactor into a constant temperature oil bath pot and keep it at a constant temperature of 60°C for 10 hours. Then, open the lid and evaporate the solvent to obtain a metal powder precursor with uniform color.

[0110] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tin-indium bimetallic element doped ruthenium oxide nanomaterial, wherein the indium doping amount is calculated as follows: n(In%) = N In / (N In +N Sn +N Ru )*100%=10%. The calculation formula of tin doping amount is: n(Sn%)=N Sn / (N In +N Sn +N Ru )*100%=20%.

[0111] Characterization of SnIn bimetallic doped ruthenium oxide materials:

[0112] The XRD pattern of the obtained tin-indium bimetallic doped ruthenium oxide material is shown in the attached Figure 6 ,from Figure 6 It can be seen that the tin-indium bimetallic doped ruthenium oxide nanomaterial exhibits the characteristic peaks of rutile phase ruthenium oxide. And there are no diffraction peaks of any other oxides, indicating that tin and indium are successfully doped into the lattice of ruthenium oxide, and the increase in the doping amount will not lead to the generation of phase separation. Because the radius of the doped indium and tin is larger than that of ruthenium, the XRD peaks are all shifted negatively, indicating that indium and tin are indeed doped into the ruthenium dioxide lattice, which has a certain impact on the ruthenium dioxide lattice, thereby changing its performance as an anode material for electrolysis of water. That is, in the tin-indium bimetallic doped ruthenium oxide nanomaterial, the tin and indium doped ruthenium oxide lattice replace the position of ruthenium in part of the lattice.

[0113] Example 5 - Tin-Bimetallic Elements Doped Ruthenium Dioxide

[0114] (1) Prepare 15 mg / mL of tin chloride ethanol solution, bismuth chloride ethanol solution and ruthenium acetylacetonate solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element, control the concentration of ruthenium acetylacetonate in the reactor to be 0.15 mol / L, the concentration of tin chloride to be 0.075 mol / L, and the concentration of bismuth chloride to be 0.025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0115] Then, add the multidentate ligand polymer polyamide to the solution, continue to seal and ultrasonicate for several hours to obtain a mixed solution with uniform color. Then, put the glass reactor into a constant temperature oil bath pot and keep it at a constant temperature of 60°C for 12 hours. Then, open the lid and evaporate the solvent to obtain a metal powder precursor with uniform color.

[0116] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tin-bismuth bimetallic element doped ruthenium oxide nanomaterial, wherein the bismuth doping amount is calculated as follows: n(Bi%)=N Bi / (N Bi +N Sn +N Ru )*100%=10%. The calculation formula of tin doping amount is: n(Sn%)=N Sn / (N Bi +N Sn +N Ru )*100%=30%.

[0117] Characterization of Sn-Bi bimetallic doped ruthenium oxide materials:

[0118] The high-resolution electron microscopy image of the obtained tin-bismuth bimetallic doped ruthenium oxide material is shown in the attached Figure 7 , Figure 7 The 0.328nm corresponds to the 110 crystal plane of ruthenium oxide. The spacing of the 110 crystal planes of ruthenium dioxide is larger than that of the conventional 0.315nm. This indicates that the addition of ions with large radius may cause the lattice expansion of ruthenium dioxide, but this method can indeed be used to add metal elements whose metal ions are much larger than ruthenium, that is, to confirm the addition of tin and bismuth metals in ruthenium dioxide.

[0119] Example 6 - Indium and Bismuth Bimetallic Elements Doped with Ruthenium Dioxide

[0120] (1) Prepare 15 mg / mL of indium chloride aqueous solution, bismuth chloride hydrochloric acid aqueous solution and nitrosoruthenium nitrate aqueous solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element, control the concentration of nitrosoruthenium nitrate aqueous solution in the reactor to be 0.2475 mol / L, the concentration of indium chloride to be 0.00125 mol / L, and the concentration of bismuth chloride to be 0.00125 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0121] Then, add the multidentate ligand polymer polypyrrole to the solution, continue to seal and ultrasonicate for several hours to obtain a mixed solution with uniform color. Then, put the glass reactor into a constant temperature oil bath pot and keep it at a constant temperature of 60°C for 12 hours. Then, open the lid and evaporate the solvent to obtain a metal powder precursor with uniform color.

[0122] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the indium-bismuth bimetallic element doped ruthenium oxide nanomaterial, wherein the bismuth doping amount is calculated as follows: n(Bi%)=N Bi / (N Bi +N In +N Ru )*100%=0.5%. The calculation formula of indium doping amount is: n(In%)=N In / (N Bi +N In +N Ru )*100%=0.5%.

[0123] Characterization of Indium Bismuth Bimetallic Doped Ruthenium Oxide Materials:

[0124] The XRD pattern of the obtained indium-bismuth bimetallic doped ruthenium oxide material is shown in the attached Figure 8 , Figure 8 It can be seen that the indium-bismuth bimetallic doped ruthenium oxide nanomaterial exhibits the characteristic peaks of rutile phase ruthenium oxide. And there are no diffraction peaks of any other oxides, indicating that bismuth and indium are successfully doped into the lattice of ruthenium oxide. Due to the addition of multidentate ligands, the metal elements are dispersed and the ruthenium phase separation will not occur. That is, in the indium-bismuth bimetallic doped ruthenium oxide nanomaterial, bismuth and indium doped ruthenium oxide lattice replace the position of ruthenium in part of the lattice.

[0125] Example 7-Titanium-Niobium Bimetallic Elements Doped Ruthenium Dioxide

[0126] (1) Prepare 15 mg / mL of titanium chloride ethanol solution, niobium chloride ethanol solution and ruthenium chloride ethanol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.175 mol / L, titanium chloride concentration to be 0.025 mol / L, and niobium chloride concentration to be 0.05 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0127] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 60°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0128] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the titanium-niobium bimetallic element doped ruthenium oxide nanomaterial, wherein the titanium doping amount is calculated as follows: n(Ti%)=N Ti / (N Ti +N Nb +N Ru )*100%=10%. The formula for calculating the niobium doping amount is: n(Nb%)=N Nb / (N Nb +N Ti +N Ru )*100%=20%.

[0129] Characterization of titanium-niobium bimetallic doped ruthenium oxide materials:

[0130] The XRD pattern of the obtained titanium-niobium bimetallic doped ruthenium oxide material is shown in the attached Fig. 9 , Fig. 9 It can be seen that the obtained titanium-niobium bimetallic doped ruthenium oxide material exhibits the characteristic peaks of rutile phase ruthenium oxide. And there are no diffraction peaks of any other oxides, indicating that titanium and niobium are successfully doped into the lattice of ruthenium oxide, and the increase in the doping amount will not lead to phase separation. That is, the titanium and niobium doped ruthenium oxide lattice in the titanium-niobium bimetallic doped ruthenium oxide nanomaterial replaces the position of ruthenium in part of the lattice.

[0131] Example 8 - Titanium-Tantalum bimetallic elements doped with ruthenium dioxide

[0132] (1) Prepare 15 mg / mL of titanium chloride ethanol solution, tantalum chloride n-butanol solution and ruthenium chloride ethanol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.225 mol / L, titanium chloride concentration to be 0.0125 mol / L, and tantalum chloride concentration to be 0.0125 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0133] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 60°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0134] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the titanium-tantalum bimetallic element doped ruthenium oxide nanomaterial, wherein the titanium doping amount is calculated as follows: n(Ti%)=N Ti / (N Ti +N Ta +N Ru )*100%=5%. The calculation formula of tantalum doping amount is: n(Ta%)=N Ta / (N Ti +N Ta +N Ru )*100%=5%.

[0135] Characterization of titanium-tantalum bimetallic doped ruthenium oxide materials:

[0136] The scanning electron microscope image of the obtained titanium-tantalum bimetallic doped ruthenium oxide material is shown in the attached Fig.10 , Fig.10 It can be seen that the obtained titanium-tantalum bimetallic doped ruthenium oxide material has a small particle size and is evenly distributed.

[0137] Example 9-Titanium-manganese bimetallic element doped ruthenium dioxide

[0138] (1) Prepare 15 mg / mL of titanium chloride ethanol solution, manganese chloride ethanol solution and ruthenium chloride ethanol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, titanium chloride concentration to be 0.0375 mol / L, and manganese chloride concentration to be 0.0125 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0139] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 60°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0140] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the titanium-manganese bimetallic element doped ruthenium oxide nanomaterial, wherein the titanium doping amount is calculated as follows: n(Ti%) = N Ti / (N Ti +N Mn +N Ru )*100%=15%. The formula for calculating the amount of manganese doping is: n(Mn%)=N Mn / (N Ti +N Mn +N Ru )*100%=5%.

[0141] Characterization of titanium-manganese bimetallic doped ruthenium oxide materials:

[0142] The scanning electron microscope image of the titanium-manganese bimetallic doped ruthenium oxide material obtained is shown in the attached Fig.11 , Fig.11 It can be seen that the obtained titanium-manganese bimetallic doped ruthenium oxide material is still rough and porous, and is evenly distributed.

[0143] Example 10 - Titanium-platinum bimetallic element doped ruthenium dioxide

[0144] (1) Prepare 15 mg / mL titanium chloride ethanol solution, chloroplatinic acid solution and ruthenium chloride ethanol solution respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.175 mol / L, titanium chloride concentration to 0.0725 mol / L, and chloroplatinic acid concentration to 0.0025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0145] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 60°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0146] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample. Wash it with deionized water and ethanol several times and dry it to obtain the titanium-platinum bimetallic element doped ruthenium oxide nanomaterial, wherein the titanium doping amount is calculated as follows: n(Ti%)=N Ti / (N Ti +N Pt +N Ru )*100%=29%. The calculation formula of platinum doping amount is: n(Pt%)=N Pt / (N Ti +N Pt +N Ru )*100%=1%.

[0147] Characterization of titanium-platinum bimetallic doped ruthenium oxide materials:

[0148] The XRD pattern of the obtained titanium-platinum bimetallic doped ruthenium oxide material is shown in the attached Fig.12 , Fig.12 It can be seen that titanium and platinum in the obtained titanium-platinum bimetallic doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide, and the increase in the doping amount does not lead to phase separation. That is, the titanium and platinum doped ruthenium oxide lattice in the titanium-platinum bimetallic doped ruthenium oxide nanomaterial replaces the position of ruthenium in part of the lattice.

[0149] Example 11-Titanium-Palladium Bimetallic Elements Doped with Ruthenium Dioxide

[0150] (1) Prepare 15 mg / mL titanium chloride ethanol solution, palladium chloride solution and ruthenium chloride ethanol solution respectively, and according to the required molar ratio of each element, add the corresponding solution volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.225 mol / L, titanium chloride concentration to 0.0025 mol / L, and palladium chloride concentration to 0.0225 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0151] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 60°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0152] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the titanium-palladium bimetallic element doped ruthenium oxide nanomaterial, wherein the titanium doping amount is calculated as follows: n(Ti%)=N Ti / (N Ti +N Pd +N Ru )*100%=1%. The calculation formula of palladium doping amount is: n(Pd%)=N Pd / (N Ti +N Pd +N Ru )*100%=9%.

[0153] Characterization of titanium-palladium bimetallic doped ruthenium oxide materials:

[0154] The scanning electron microscope image of the obtained titanium-palladium bimetallic doped ruthenium oxide material is shown in the attached Fig.13 , Fig.13 It can be seen that the obtained titanium-palladium bimetallic doped ruthenium oxide material is rough, porous and evenly distributed.

[0155] Example 12-Titanium-Cobalt Bimetallic Elements Doped Ruthenium Dioxide

[0156] (1) Prepare 15 mg / mL titanium chloride alcohol solution, cobalt chloride solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, titanium chloride concentration to be 0.025 mol / L, and cobalt chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0157] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 60°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0158] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the titanium-cobalt bimetallic element doped ruthenium oxide nanomaterial, wherein the titanium doping amount is calculated as follows: n(Ti%) = N Ti / (N Ti +N Co +N Ru )*100%=10%. The formula for calculating the cobalt doping amount is: n(Co%)=N Ti / (N Ti +N Co +N Ru )*100%=10%.

[0159] Characterization of titanium-cobalt bimetallic doped ruthenium oxide materials:

[0160] The XRD pattern of the obtained titanium-cobalt bimetallic doped ruthenium oxide material is shown in the attached Fig.14 , Fig.14 It can be seen that the titanium and cobalt in the obtained titanium-cobalt bimetallic doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, the titanium and cobalt doped inside the ruthenium oxide lattice in the titanium-cobalt bimetallic doped ruthenium oxide nanomaterial replace the position of ruthenium in part of the lattice.

[0161] Example 13 - Niobium and Tantalum Bimetallic Elements Doped with Ruthenium Dioxide

[0162] (1) Prepare 15 mg / mL of niobium chloride alcohol solution, tantalum chloride alcohol solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2375 mol / L, niobium chloride concentration to be 0.00625 mol / L, and tantalum chloride concentration to be 0.00625 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0163] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0164] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the niobium-tantalum bimetallic element doped ruthenium oxide nanomaterial, wherein the niobium doping amount is calculated as follows: n(Nb%)=N Nb / (N Nb +N Ta +N Ru )*100%=2.5%. The calculation formula of tantalum doping amount is: n(Ta%)=N Ta / (N Nb +N Ta +N Ru )*100%=2.5%.

[0165] Characterization of niobium-tantalum bimetallic doped ruthenium oxide materials:

[0166] The scanning electron microscope image of the obtained niobium-tantalum bimetallic doped ruthenium oxide material is shown in the attached Fig.15 , Fig.15 It can be seen that the obtained niobium-tantalum bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0167] Example 14 - Niobium and manganese bimetallic elements doped with ruthenium dioxide

[0168] (1) Prepare 15 mg / mL of niobium chloride alcohol solution, manganese chloride alcohol solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, niobium chloride concentration to be 0.025 mol / L, and manganese chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0169] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0170] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the niobium-manganese bimetallic element doped ruthenium oxide nanomaterial, wherein the niobium doping amount is calculated as follows: n(Nb%)=N Nb / (N Nb +N Mn +N Ru )*100%=10%. The formula for calculating the amount of manganese doping is: n(Mn%)=N Mn / (N Nb +N Mn +N Ru )*100%=10%.

[0171] Characterization of niobium-manganese bimetallic doped ruthenium oxide materials:

[0172] The element distribution diagram of the obtained niobium-manganese bimetallic doped ruthenium oxide material is shown in the attached Fig.16 , Fig.16 It can be seen that the various elements of the obtained niobium-manganese bimetallic doped ruthenium oxide material are evenly distributed, and the distribution of niobium, manganese and ruthenium is consistent throughout the particles. This shows that niobium and manganese are evenly dispersed inside the ruthenium oxide lattice. Therefore, niobium, manganese and ruthenium are evenly dispersed in the niobium-manganese bimetallic doped ruthenium oxide nanomaterial, and the detected ratio of each element is basically consistent with the feed ratio.

[0173] The XRD pattern of the obtained niobium-manganese bimetallic doped ruthenium oxide material is shown in the attached Fig.17 , Fig.17It can be seen that niobium and manganese in the obtained niobium-manganese bimetallic doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, the niobium and manganese doped ruthenium oxide lattice in the niobium-manganese bimetallic doped ruthenium oxide nanomaterial replaces the position of ruthenium in part of the lattice. And because the niobium radius is large and the manganese radius is small, the two are coordinated and neutralized, making its XRD peak shape basically similar to that of conventional ruthenium dioxide.

[0174] Example 15 - Niobium-chromium bimetallic elements doped with ruthenium dioxide

[0175] (1) Prepare 15 mg / mL of niobium chloride alcohol solution, chromium chloride alcohol solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, niobium chloride concentration to be 0.025 mol / L, and chromium chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0176] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0177] (2) Put the metal powder precursor obtained in step (1) into a porcelain boat, and then put the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the niobium-chromium bimetallic element doped ruthenium oxide nanomaterial, wherein the niobium doping amount is calculated as follows: n(Nb%)=N Nb / (N Nb +N Cr +N Ru )*100%=10%. The calculation formula of chromium doping amount is: n(Cr%)=N Cr / (N Nb +N Cr +N Ru )*100%=10%.

[0178] Characterization of niobium-chromium bimetallic doped ruthenium oxide materials:

[0179] The XRD pattern of the obtained niobium-chromium bimetallic doped ruthenium oxide material is shown in the attached Fig.18 , Fig.18It can be seen that niobium and chromium in the obtained niobium-chromium bimetallic doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, the niobium and chromium doped inside the ruthenium oxide lattice in the niobium-chromium bimetallic doped ruthenium oxide nanomaterial replace the position of ruthenium in part of the lattice.

[0180] Example 16 - Niobium-palladium bimetallic element doped ruthenium dioxide

[0181] (1) Prepare 15 mg / mL of niobium chloride alcohol solution, palladium chloride alcohol solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.125 mol / L, niobium chloride concentration to be 0.01 mol / L, and palladium chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0182] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0183] (2) Put the metal powder precursor obtained in step (1) into a porcelain boat, and then put the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the niobium-palladium bimetallic element doped ruthenium oxide nanomaterial, wherein the niobium doping amount is calculated as follows: n(Nb%)=N Nb / (N Nb +N Pd +N Ru )*100%=40%. The calculation formula of palladium doping amount is: n(Pd%)=N Pd / (N Nb +N Pd +N Ru )*100%=10%.

[0184] Characterization of niobium-palladium bimetallic doped ruthenium oxide materials:

[0185] The scanning electron microscope image of the obtained niobium-palladium bimetallic doped ruthenium oxide material is shown in the attached Fig.19 , Fig.19 It can be seen that the obtained niobium-palladium bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0186] Example 17 - Niobium and Cobalt Bimetallic Elements Doped Ruthenium Dioxide

[0187] (1) Prepare 15 mg / mL of niobium chloride alcohol solution, cobalt chloride solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, niobium chloride concentration to be 0.025 mol / L, and cobalt chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0188] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0189] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the niobium-cobalt bimetallic element doped ruthenium oxide nanomaterial, wherein the niobium doping amount is calculated as follows: n(Nb%)=N Nb / (N Nb +N Co +N Ru )*100%=10%. The formula for calculating the cobalt doping amount is: n(Co%)=N Co / (N Nb +N Co +N Ru )*100%=10%.

[0190] Characterization of niobium-cobalt bimetallic doped ruthenium oxide materials:

[0191] The XRD pattern of the obtained niobium-cobalt bimetallic doped ruthenium oxide material is shown in the attached Fig. 20 , Fig. 20 It can be seen that niobium and cobalt in the obtained niobium-cobalt bimetallic doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, niobium and cobalt doped into the ruthenium oxide lattice in the niobium-cobalt bimetallic doped ruthenium oxide nanomaterial replace the position of ruthenium in part of the lattice.

[0192] Example 18 - Tantalum and manganese bimetallic elements doped with ruthenium dioxide

[0193] (1) Prepare 15 mg / mL of tantalum chloride alcohol solution, manganese chloride solution and ruthenium chloride alcohol solution respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.2 mol / L, tantalum chloride concentration to 0.025 mol / L, and manganese chloride concentration to 0.025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0194] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0195] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tantalum-manganese bimetallic element doped ruthenium oxide nanomaterial, wherein the tantalum doping amount is calculated as follows: n(Ta%)=N Ta / (N Ta +N Mn +N Ru )*100%=10%. The formula for calculating the amount of manganese doping is: n(Mn%)=N Mn / (N Ta +N Mn +N Ru )*100%=10%.

[0196] Characterization of Tantalum-Manganese bimetallic doped ruthenium oxide materials:

[0197] The scanning electron microscope image of the obtained tantalum-manganese bimetallic doped ruthenium oxide material is shown in the attached Fig.21 , Fig.21 It can be seen that the obtained tantalum-manganese bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0198] Example 19 - Tantalum-Platinum Bimetallic Elements Doped with Ruthenium Dioxide

[0199] (1) Prepare 15 mg / mL of tantalum chloride alcohol solution, chloroplatinic acid solution and ruthenium chloride alcohol solution respectively, and put the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.125 mol / L, tantalum chloride concentration to be 0.0625 mol / L, and chloroplatinic acid concentration to be 0.0625 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0200] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0201] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tantalum-platinum bimetallic element doped ruthenium oxide nanomaterial, wherein the tantalum doping amount is calculated as follows: n(Ta%)=N Ta / (N Ta +N Pt +N Ru )*100%=25%. The calculation formula of platinum doping amount is: n(Pt%)=N Pt / (N Ta +N Pt +N Ru )*100%=25%.

[0202] Characterization of Tantalum-Platinum bimetallic doped ruthenium oxide materials:

[0203] The scanning electron microscope image of the obtained tantalum-platinum bimetallic doped ruthenium oxide material is shown in the attached Fig. 22 , Fig. 22 It can be seen that the obtained tantalum-platinum bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0204] Example 20 - Tantalum-Chromium Bimetallic Elements Doped Ruthenium Dioxide

[0205] (1) Prepare 15 mg / mL of tantalum chloride alcohol solution, chromium chloride solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, tantalum chloride concentration to be 0.025 mol / L, and chromium chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0206] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0207] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tantalum-chromium bimetallic element doped ruthenium oxide nanomaterial, wherein the tantalum doping amount is calculated as follows: n(Ta%)=N Ta / (N Ta +N Cr +N Ru )*100%=10%. The calculation formula of chromium doping amount is: n(Cr%)=N Cr / (N Ta +N Cr +N Ru )*100%=10%.

[0208] Characterization of Tantalum-Chromium Bimetallic Doped Ruthenium Oxide Materials:

[0209] The XRD pattern of the obtained tantalum-chromium bimetallic doped ruthenium oxide material is shown in the attached Fig.23 , Fig.23 It can be seen that the tantalum and chromium in the obtained tantalum-chromium bimetallic doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, the tantalum and chromium doped ruthenium oxide lattice in the tantalum-chromium bimetallic doped ruthenium oxide nanomaterial replace the position of ruthenium in part of the lattice.

[0210] Example 21 - Tantalum-Cobalt Bimetallic Elements Doped Ruthenium Dioxide

[0211] (1) Prepare 15 mg / mL of tantalum chloride alcohol solution, cobalt chloride solution and ruthenium chloride alcohol solution respectively, and according to the required molar ratio of each element, add the corresponding solution volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.2 mol / L, tantalum chloride concentration to 0.025 mol / L, and cobalt chloride concentration to 0.025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0212] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0213] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tantalum-cobalt bimetallic element doped ruthenium oxide nanomaterial, wherein the tantalum doping amount is calculated as follows: n(Ta%)=N Ta / (N Ta +N Co +N Ru )*100%=10%. The formula for calculating the cobalt doping amount is: n(Co%)=N Co / (N Ta +N Co +N Ru )*100%=10%.

[0214] Characterization of Tantalum-Cobalt Bimetallic Doped Ruthenium Oxide Materials:

[0215] The XRD pattern of the obtained tantalum-cobalt bimetallic doped ruthenium oxide material is shown in the attached Fig.24 , Fig.24 It can be seen that the tantalum and cobalt in the obtained tantalum-cobalt bimetallic doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, the tantalum and cobalt doped ruthenium oxide lattice in the tantalum-cobalt bimetallic doped ruthenium oxide nanomaterial replace the position of ruthenium in part of the lattice.

[0216] Example 22-Nibium, manganese, cobalt, tantalum and other metal elements doped with ruthenium dioxide

[0217] (1) Prepare 15 mg / mL of niobium chloride alcohol solution, manganese chloride solution, tantalum chloride alcohol solution, cobalt chloride solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.15 mol / L, niobium chloride concentration to be 0.025 mol / L, manganese chloride concentration to be 0.025 mol / L, tantalum chloride concentration to be 0.025 mol / L, and cobalt chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0218] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0219] (2) Put the metal powder precursor obtained in step (1) into a porcelain boat, and then put the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the niobium-manganese-cobalt-tantalum multi-metal element doped ruthenium oxide nanomaterial, wherein the niobium doping amount is calculated as follows: n(Nb%)=N Nb / (N Nb +N Mn +N Ta +N Co +N Ru )*100%=10%. The formula for calculating the amount of manganese doping is: n(Mn%)=N Mn / (N Nb +N Mn +N Ta +N Co +N Ru )*100%=10%. The formula for calculating the tantalum doping amount is: n(Ta%)=N Ta / (N Nb +N Mn +N Ta +N Co +N Ru )*100%=10%. The formula for calculating the cobalt doping amount is: n(Co%)=N Co / (N Nb +N Mn +N Ta +N Co +N Ru )*100%=10%.

[0220] Characterization of niobium, manganese, cobalt and tantalum multi-metal doped ruthenium oxide materials:

[0221] The XRD pattern of the obtained niobium-manganese-cobalt-tantalum multi-metal doped ruthenium oxide material is shown in the attached Fig.25 , Fig.25 It can be seen that niobium, manganese, tantalum and cobalt in the obtained multi-metal doped ruthenium oxide materials with different radii, electronegativity and redox activity of niobium, manganese, cobalt and tantalum are successfully doped into the lattice of ruthenium oxide without phase separation. That is, in the 40% high metal doping amount niobium, manganese, tantalum and cobalt multi-metal doped ruthenium oxide nanomaterial, the niobium, manganese, tantalum and cobalt doped ruthenium oxide lattice replace the position of ruthenium in part of the lattice.

[0222] The element distribution diagram of the obtained niobium-manganese-cobalt-tantalum multi-metal doped ruthenium oxide material is shown in the attached Fig.26 , Fig.26 It can be seen that the various elements of the obtained niobium-manganese-cobalt-tantalum multi-metal doped ruthenium oxide material are evenly distributed, and the distribution of niobium, manganese, cobalt, tantalum and ruthenium is consistent throughout the particles. This shows that niobium, manganese, cobalt and tantalum are evenly dispersed inside the ruthenium oxide lattice. Therefore, niobium, manganese, cobalt, tantalum and ruthenium are evenly dispersed in the niobium-manganese-cobalt-tantalum multi-metal doped ruthenium oxide nanomaterial.

[0223] Example 23-NbO2-MnV-Ga multi-metallic element doped ruthenium dioxide

[0224] (1) Prepare 15 mg / mL of niobium chloride alcohol solution, manganese chloride solution, vanadium chloride alcohol solution, gallium nitrate solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element, and control the concentration of ruthenium chloride solution in the reactor to be 0.175 mol / L, niobium chloride concentration to be 0.025 mol / L, manganese chloride concentration to be 0.0125 mol / L, vanadium chloride concentration to be 0.0125 mol / L, and gallium nitrate concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0225] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0226] (2) Put the metal powder precursor obtained in step (1) into a porcelain boat, and then put the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the niobium manganese vanadium gallium multi-metal element doped ruthenium oxide nanomaterial, wherein the niobium doping amount is calculated as follows: n(Nb%)=N Nb / (N Nb +N Mn +N V +N Ga +N Ru )*100%=10%. The formula for calculating the amount of manganese doping is: n(Mn%)=N Mn / (N Nb +N Mn +N V +N Ga +N Ru )*100%=5%. The calculation formula of vanadium doping amount is: n(V%)=N V / (N Nb +N Mn +N V +N Ga +N Ru )*100%=5%. The formula for calculating the gallium doping amount is: n(Ga%)=N Ga / (N Nb +N Mn +N V +N Ga +N Ru )*100%=10%.

[0227] Characterization of niobium-manganese-vanadium-gallium multi-metal doped ruthenium oxide materials:

[0228] The XRD pattern of the obtained niobium-manganese-vanadium-gallium multi-metal doped ruthenium oxide material is shown in the attached Fig. 27 , Fig. 27 It can be seen that niobium, manganese, vanadium and gallium in the obtained niobium-manganese-vanadium-gallium multi-metal doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, in the niobium-manganese-vanadium-gallium multi-metal doped ruthenium oxide nanomaterial with a metal doping amount of 30%, niobium, manganese, vanadium and gallium doped into the ruthenium oxide lattice replace the position of ruthenium in part of the lattice.

[0229] The element distribution diagram of the obtained niobium-manganese-vanadium-gallium multi-metal doped ruthenium oxide material is shown in the attached Fig.28 , Fig.28It can be seen that the various elements of the obtained niobium manganese vanadium gallium multi-metal doped ruthenium oxide material are evenly distributed, and the distribution of niobium, manganese, vanadium, gallium and ruthenium is consistent throughout the particle. This shows that niobium, manganese, vanadium and gallium are evenly dispersed inside the ruthenium oxide lattice. Therefore, niobium, manganese, vanadium, gallium and ruthenium are evenly dispersed in the niobium manganese vanadium gallium multi-metal doped ruthenium oxide nanomaterial. Moreover, the multi-metal elements from different periods and different main groups are not mutually exclusive and can be well dispersed in the ruthenium dioxide lattice.

[0230] Example 24-Ga-Cr bimetallic elements doped with ruthenium dioxide

[0231] (1) Prepare gallium chloride alcohol solution, chromium chloride solution and ruthenium chloride alcohol solution of 15 mg / mL respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.225 mol / L, gallium chloride concentration to 0.0125 mol / L, and chromium chloride concentration to 0.0125 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0232] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0233] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the gallium-chromium bimetallic element doped ruthenium oxide nanomaterial, wherein the gallium doping amount is calculated as follows: n(Ga%) = N Ga / (N Ga +N Cr +N Ru )*100%=5%. The calculation formula of chromium doping amount is: n(Cr%)=N Cr / (N Ga +N Cr +N Ru )*100%=5%.

[0234] Characterization of gallium-chromium bimetallic doped ruthenium oxide materials:

[0235] The scanning electron microscope image of the obtained gallium-chromium bimetallic doped ruthenium oxide material is shown in the attached Fig.29 , Fig.29 It can be seen that the obtained gallium-chromium bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0236] Example 25-Ga-Ti bimetallic elements doped with ruthenium dioxide

[0237] (1) Prepare gallium chloride alcohol solution, titanium chloride solution and ruthenium chloride alcohol solution of 15 mg / mL respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.2 mol / L, gallium chloride concentration to 0.025 mol / L, and titanium chloride concentration to 0.025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0238] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0239] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the gallium-titanium bimetallic element doped ruthenium oxide nanomaterial, wherein the gallium doping amount is calculated as follows: n(Ga%) = N Ga / (N Ga +N Ti +N Ru )*100%=10%. The calculation formula of titanium doping amount is: n(Ti%)=N Ti / (N Ga +N Ti +N Ru )*100%=10%.

[0240] Characterization of gallium-titanium bimetallic doped ruthenium oxide materials:

[0241] The scanning electron microscope image of the obtained gallium-titanium bimetallic doped ruthenium oxide material is shown in the attached Fig.30 , Fig.30 It can be seen that the obtained gallium-titanium bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0242] Example 26-Ga-Mn bimetallic elements doped with ruthenium dioxide

[0243] (1) Prepare gallium nitrate alcohol solution, manganese nitrate solution and ruthenium chloride alcohol solution of 15 mg / mL respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.175 mol / L, gallium nitrate concentration to 0.0375 mol / L, and manganese nitrate concentration to 0.0375 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0244] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0245] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the gallium-manganese bimetallic element doped ruthenium oxide nanomaterial, wherein the gallium doping amount is calculated as follows: n(Ga%) = N Ga / (N Ga +N Mn +N Ru )*100%=15%. The formula for calculating the amount of manganese doping is: n(Mn%)=N Mn / (N Ga +N Mn +N Ru )*100%=15%.

[0246] Characterization of GaMn bimetallic doped ruthenium oxide materials:

[0247] The XRD pattern of the obtained gallium-manganese metal-doped ruthenium oxide material is shown in the attached Fig.31 , Fig.31 It can be seen that manganese and gallium in the obtained gallium-manganese metal-doped ruthenium oxide material are successfully doped into the lattice of ruthenium oxide without phase separation. That is, manganese and gallium doped inside the ruthenium oxide lattice in the manganese-gallium metal-doped ruthenium oxide nanomaterial replace the position of ruthenium in part of the lattice.

[0248] Example 27-Sn-Cr bimetallic elements doped with ruthenium dioxide

[0249] (1) Prepare 15 mg / mL of tin chloride alcohol solution, chromium chloride solution and ruthenium chloride alcohol solution respectively, and put the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, tin chloride concentration to be 0.025 mol / L, and chromium chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0250] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0251] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tin-chromium bimetallic element doped ruthenium oxide nanomaterial, wherein the tin doping amount is calculated as follows: n(Sn%)=N Sn / (N Sn +N Cr +N Ru )*100%=10%. The calculation formula of chromium doping amount is: n(Cr%)=N Cr / (N Sn +N Cr +N Ru )*100%=10%.

[0252] Characterization of Sn-Cr bimetallic doped ruthenium oxide materials:

[0253] The scanning electron microscope image of the obtained tin-chromium bimetallic doped ruthenium oxide material is shown in the attached Fig.32 , Fig.32 It can be seen that the obtained tin-chromium bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0254] Example 28-Sn / Nb bimetallic elements doped with ruthenium dioxide

[0255] (1) Prepare 15 mg / mL of tin chloride alcohol solution, niobium chloride solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.2 mol / L, tin chloride concentration to be 0.025 mol / L, and niobium chloride concentration to be 0.025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0256] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0257] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours, and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tin-niobium bimetallic element doped ruthenium oxide nanomaterial, wherein the tin doping amount is calculated as follows: n(Sn%)=N Sn / (N Sn +N Nb +N Ru )*100%=10%. The formula for calculating the niobium doping amount is: n(Nb%)=N Nb / (N Sn +N Nb +N Ru )*100%=10%.

[0258] Characterization of Sn-Nb bimetallic doped ruthenium oxide materials:

[0259] The XRD pattern of the obtained Sn-Nb bimetallic doped ruthenium oxide material is shown in the attached Fig.33 , Fig.33 It can be seen that the tin and niobium in the obtained tin-niobium bimetallic doped ruthenium oxide material are successfully doped into the ruthenium oxide lattice without phase separation. That is, the tin and niobium doped ruthenium oxide lattice in the tin-niobium metal doped ruthenium oxide nanomaterial replaces the position of ruthenium in part of the lattice.

[0260] Example 29-Sn / Tantalum Bimetallic Elements Doped Ruthenium Dioxide

[0261] (1) Prepare 15 mg / mL of tin chloride alcohol solution, tantalum chloride solution and ruthenium chloride alcohol solution respectively, and add the corresponding volume of metal salt solution into a 20 ml glass reactor according to the required molar ratio of each element. Control the concentration of ruthenium chloride solution in the reactor to be 0.225 mol / L, tin chloride concentration to be 0.02475 mol / L, and tantalum chloride concentration to be 0.00025 mol / L. Seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0262] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0263] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tin-tantalum bimetallic element doped ruthenium oxide nanomaterial, wherein the tin doping amount is calculated as follows: n(Sn%)=N Sn / (N Sn +N Ta +N Ru )*100%=9.9%. The calculation formula of tantalum doping amount is: n(Ta%)=N Ta / (N Sn +N Ta +N Ru )*100%=0.1%.

[0264] Characterization of Sn / Tantalum bimetallic doped ruthenium oxide materials:

[0265] The XRD pattern of the obtained tin-tantalum bimetallic doped ruthenium oxide material is shown in the attached Fig.34 , Fig.34 It can be seen that the tin and tantalum in the obtained tin-tantalum bimetallic doped ruthenium oxide material are successfully doped into the ruthenium oxide lattice without phase separation. That is, the tin and tantalum doped ruthenium oxide lattice in the tin-tantalum metal doped ruthenium oxide nanomaterial replaces the position of ruthenium in part of the lattice.

[0266] Example 30-Tin-Cobalt Bimetallic Elements Doped Ruthenium Dioxide

[0267] (1) Prepare 15 mg / mL of tin chloride alcohol solution, cobalt chloride solution and ruthenium chloride alcohol solution respectively, and according to the required molar ratio of each element, add the corresponding volume of metal salt solution into a 20 ml glass reactor, control the concentration of ruthenium chloride solution in the reactor to 0.2 mol / L, tin chloride concentration to 0.025 mol / L, and cobalt chloride concentration to 0.025 mol / L, and seal the lid of the glass reactor to prevent hydrolysis of the precursor. After dispersing the sealed glass reactor under ultrasonic conditions for several hours, a multi-metal solution with uniform color is obtained.

[0268] Then, polyvinyl pyrrolidone, a multidentate ligand polymer, was added to the solution, and the mixture was sealed and ultrasonicated for several hours to obtain a uniform color mixed solution. Then, the glass reactor was placed in a constant temperature oil bath pot and kept at a constant temperature of 80°C for 12 hours. Subsequently, the lid was opened and the solvent was evaporated to obtain a uniform color metal powder precursor.

[0269] (2) Place the metal powder precursor obtained in step (1) into a porcelain boat, and then place the porcelain boat containing the metal powder precursor into a muffle furnace; set the heating rate to 10°C / min, heat to 300°C-500°C, keep warm for 3-6 hours and then cool naturally to obtain a black powder sample, wash it with deionized water and ethanol several times and dry it to obtain the tin-cobalt bimetallic element doped ruthenium oxide nanomaterial, wherein the tin doping amount is calculated as follows: n(Sn%)=N Sn / (N Sn +N Co +N Ru )*100%=10%. The formula for calculating the cobalt doping amount is: n(Co%)=N Co / (N Sn +N Co +N Ru )*100%=10%.

[0270] Characterization of SnCo bimetallic doped ruthenium oxide materials:

[0271] The scanning electron microscope image of the obtained tin-cobalt bimetallic doped ruthenium oxide material is shown in the attached Fig.35 , Fig.35 It can be seen that the obtained tin-cobalt bimetallic doped ruthenium oxide material is evenly distributed and has a size between 50-200nm.

[0272] Application Example 1

[0273] The electrolytic water oxygen evolution performance of the ruthenium oxide nanomaterial doped with two or more p-region metals (P) of the present invention was tested using a three-electrode system: the reference electrode was a silver / silver chloride electrode, the counter electrode was a platinum sheet electrode, and the working electrode was two or more p-region metal (P)-doped ruthenium oxide nanomaterials or commercial ruthenium dioxide obtained in Table 1. The test was carried out in a 0.5 mol / L sulfuric acid solution. The polarization curve obtained was as shown in FIG. Fig.36 shown.

[0274] from Fig.36 It can be seen that the ruthenium oxide nanomaterials doped with two or more p-zone metals (P) obtained in Examples 1, 3 and 6 can maintain the crystal form of ruthenium dioxide regardless of low or high doping amount when doped with different metals and at different doping amounts, and have good electrolytic water oxygen evolution performance ( Fig.36 curve AC), which is significantly better than the commercial ruthenium dioxide material ( Fig.36 Curve D), at a current density of 10 mA per square centimeter, the overpotentials are 174 mV, 203 mV, and 228 mV, respectively, which is lower than 346 mV of commercial ruthenium dioxide.

[0275] Fig.37 The present invention provides stability curves of ruthenium oxide nanomaterials doped with two or more p-zone metals (P) obtained in Examples 1, 3 and 6 of the present invention as oxygen evolution anode materials in 0.5 mol / L H2SO4 solution; wherein curve A is the stability curve of the gallium-indium dual-doped ruthenium oxide material obtained in Example 1 at a current density of 100 mA per square centimeter, curve B is the stability curve of the gallium-bismuth dual-doped ruthenium oxide material obtained in Example 3 at a current density of 100 mA per square centimeter, curve C is the stability curve of the indium-bismuth dual-doped ruthenium oxide material obtained in Example 6 at a current density of 200 mA per square centimeter, and curve D is the stability curve of the commercial ruthenium oxide material at a current density of 100 mA per square centimeter.

[0276] Fig.37 It can be seen that the gallium-indium dual-doped ruthenium oxide material is maintained at a current density of 100 mA per square centimeter for 550 hours, the gallium-bismuth dual-doped ruthenium oxide material is maintained at a current density of 100 mA per square centimeter for 270 hours, and the indium-bismuth dual-doped ruthenium oxide material is maintained at a current density of 200 mA per square centimeter for 130 hours. The current of the two or more p-region metal (P)-doped ruthenium oxide nanomaterials obtained in Examples 1, 3 and 6 is almost not attenuated, indicating that the two or more p-region metal (P)-doped ruthenium oxide nanomaterials have extremely high stability at high current density when used as anode materials for oxygen evolution reaction. And the stability is much better than commercial ruthenium dioxide (commercial ruthenium dioxide is maintained at a current density of 100 mA per square centimeter for 9 hours).

[0277] Application Example 2

[0278] The electrolytic water oxygen evolution performance of the two or more transition metal (T) doped ruthenium oxide nanomaterials of the present invention is tested using a three-electrode system: the reference electrode is a silver / silver chloride electrode, the counter electrode is a platinum sheet electrode, and the working electrode is two or more transition metal (T) doped ruthenium oxide nanomaterials obtained in Table 2 or commercial ruthenium dioxide. The test is carried out in a 0.5 mol / L sulfuric acid solution, and the obtained polarization curve is as shown in FIG. Fig.38 shown.

[0279] from Fig.38 It can be seen that the ruthenium oxide nanomaterials doped with two or more transition metals (T) obtained in Examples 8, 14 and 17 can maintain the crystal form of ruthenium dioxide when doped with different metals and in different doping amounts, and have good electrolytic water oxygen evolution performance ( Fig.38 curve AC), which is significantly better than the commercial ruthenium dioxide material ( Fig.36 Curve D), at a current density of 10 mA per square centimeter, the overpotentials are 241 mV, 210 mV, and 231 mV, respectively, which is lower than 346 mV of commercial ruthenium dioxide.

[0280] Fig.39 The present invention provides stability curves of ruthenium oxide nanomaterials doped with two or more transition metals (T) obtained in Examples 8, 14 and 17 of the present invention as oxygen evolution anode materials in 0.5 mol / L H2SO4 solution; wherein curve A is the stability curve of the titanium-tantalum dual-doped ruthenium oxide material obtained in Example 8 at a current density of 100 mA per square centimeter, curve B is the stability curve of the niobium-manganese dual-doped ruthenium oxide material obtained in Example 14 at a current density of 200 mA per square centimeter, and curve C is the stability curve of the niobium-cobalt dual-doped ruthenium oxide material obtained in Example 17 at a current density of 100 mA per square centimeter.

[0281] Fig.39 It can be seen that the titanium-niobium dual-doped ruthenium oxide material is maintained at a current density of 100 mA per square centimeter for 145 hours, the niobium-manganese dual-doped ruthenium oxide material is maintained at a current density of 200 mA per square centimeter for 400 hours, and the niobium-cobalt dual-doped ruthenium oxide material is maintained at a current density of 100 mA per square centimeter for 100 hours. The current of the two or more transition metal (T)-doped ruthenium oxide nanomaterials obtained in Examples 8, 14 and 17 is almost not attenuated, indicating that the two or more transition metal (T)-doped ruthenium oxide nanomaterials have extremely high stability at high current density when used as anode materials for oxygen evolution reaction. And the stability is much better than commercial ruthenium dioxide (commercial ruthenium dioxide is maintained at a current density of 100 mA per square centimeter for 9 hours).

[0282] Application Example 3

[0283] The electrolytic water oxygen evolution performance of the ruthenium oxide nanomaterial doped with two or more p-region metal (P) and / or transition metal (T) oxides of the present invention was tested using a three-electrode system: the reference electrode was a silver / silver chloride electrode, the counter electrode was a platinum sheet electrode, and the working electrode was two or more p-region metal (P) and / or transition metal (T) doped ruthenium oxide nanomaterials or commercial ruthenium dioxide obtained in Table 3. The test was carried out in a 0.5 mol / L sulfuric acid solution. The obtained polarization curve is as shown in FIG. Fig.40 shown.

[0284] from Fig.40 It can be seen that the ruthenium oxide nanomaterials doped with two or more p-zone metal (P) and / or transition metal (T) oxides obtained in Examples 23, 27 and 28 can maintain the crystal form of ruthenium dioxide when different metals are doped in cross-zone combination and the doping amount is increased, and have good water electrolysis oxygen evolution performance ( Fig.40 curve AC), which is significantly better than the commercial ruthenium dioxide material ( Fig.36 Curve D), at a current density of 10 mA per square centimeter, the overpotentials are 232 mV, 175 mV, and 228 mV, respectively, which is lower than 346 mV of commercial ruthenium dioxide.

[0285] Fig.41 The present invention provides stability curves of ruthenium oxide nanomaterials doped with a combination of two or more p-zone metal (P) and / or transition metal (T) oxides obtained in Examples 23, 27 and 28 of the present invention as oxygen evolution anode materials in 0.5 mol / L H2SO4 solution; wherein curve A is the stability curve of the niobium, manganese, vanadium and gallium multi-metal doped ruthenium oxide material obtained in Example 23 at a current density of 100 mA per square centimeter, curve B is the stability curve of the tin-chromium dual-doped ruthenium oxide material obtained in Example 27 at a current density of 100 mA per square centimeter, and curve C is the stability curve of the tin-niobium dual-doped ruthenium oxide material obtained in Example 28 at a current density of 100 mA per square centimeter.

[0286] Fig.41It can be seen that the niobium-manganese-vanadium-gallium multi-metal doped ruthenium oxide material is maintained at a current density of 100 mA per square centimeter for 160 hours, the tin-chromium dual-doped ruthenium oxide material is maintained at a current density of 100 mA per square centimeter for 300 hours, and the tin-niobium dual-doped ruthenium oxide material is maintained at a current density of 100 mA per square centimeter for 90 hours. The current of the ruthenium oxide nanomaterial doped with two or more p-region metal (P) and / or transition metal (T) oxides obtained in Examples 23, 27 and 28 is almost not attenuated, indicating that the ruthenium oxide nanomaterial doped with two or more p-region metal (P) and / or transition metal (T) oxides has extremely high stability at high current density when used as an anode material for oxygen evolution reaction. And the stability is much better than commercial ruthenium dioxide (commercial ruthenium dioxide is maintained at a current density of 100 mA per square centimeter for 9 hours).

[0287] Application Example 4

[0288] Fig.42 The stability curve of the PEM device measured at 80°C is the niobium-manganese bimetallic doped ruthenium oxide material of Example 14 of the present invention as the oxygen evolution anode material and Pt / C as the cathode material. Curve B is the stability curve of the niobium-manganese bimetallic doped ruthenium oxide material. It can be found that Nb 0.1 Mn 0.1 Ru 0.8 PEM electrolyzer with O2 as anode at 500mA / cm 2 It can work stably for 1000 hours at a current density with only 59mV attenuation. Curve A is the stability curve of commercial ruthenium dioxide, which decays by about 200mV in about 4 hours. This shows that the ruthenium oxide nanomaterial doped with niobium and manganese bimetallic has extremely high stability at high current density when used as an anode material for oxygen evolution reaction. This further illustrates that the stability of the oxygen evolution reaction of the ruthenium oxide nanomaterial doped with a combination of two or more p-zone metal (P) and / or transition metal (T) oxides prepared using a polymer multidentate ligand is excellent.

[0289] The molecular formulas and application properties of the above embodiments are summarized as follows:

[0290] Table 1 Ruthenium oxide doped with p-zone metal combinations

[0291]

[0292] Table 2 Ruthenium oxide doped with transition metal combinations

[0293]

[0294]

[0295] Table 3 Ruthenium oxide co-doped with p-block metals and transition metals

[0296]

[0297] The above embodiments are merely exemplary illustrations of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals, characterized in that: Its molecular formula is one of the following: Type 1: Ruthenium oxide nanomaterials doped with two or more p-zone metals 1 x1 P 2 x2 ......P n xn Ru 1-x1-x2-......-xn O2; or Type 2: Ruthenium oxide nanomaterials doped with two or more transition metals 1 y1 T 2 y2 ......T n yn Ru 1-y1-y2-......-yn O2; or Type 3: Ruthenium oxide nanomaterials co-doped with p-zone metal (P) and transition metal (T) 1 x1 P 2 x2 ......P n xn T 1 y1 T 2 y2 ......T n yn Ru 1-x1-x2-......-xn-y1-y2-......-yn O2; Among them, P 1 x1 , P 2 x2 ,......P n xn is a p-zone metal, wherein the p-zone metal is selected from one or more of gallium, indium, germanium, tin, lead, antimony, and bismuth; T 1 y1 , T 2 y2 ,......T n yn The transition metal is selected from one or more of titanium, zirconium, hafnium, cadmium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, rhenium, iron, cobalt, nickel, copper, zinc, palladium, osmium, cerium and praseodymium.

2. The ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals according to claim 1, characterized in that: The total doping ratio, i.e. the molar ratio of the doped metal to the total metal, is 1-50%, i.e. x1+x2+......+x n +y1+y2+......y n =1~50%, but the molar ratio between each doping metal is not limited.

3. The ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals according to claim 1, characterized in that: It maintains the crystal structure of rutile phase ruthenium oxide.

4. The ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals according to claim 1, characterized in that: The nanoparticles are rough and porous nanoparticles with a size of 5 to 200 nm. The doped metal is uniformly dispersed in the nanomaterial in an atomic-level dispersion manner.

5. The method for preparing a ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals as claimed in claim 1, characterized in that: The preparation method is a sol-gel method, comprising the following steps: Step (1), placing the complex into a solution containing a ruthenium source and two or more p-block metal sources and / or transition metal sources to obtain a mixture, sealing the mixture in a container, mixing and stirring for several hours, opening the container lid, evaporating the solvent, scraping out the powder, and obtaining a metal complex precursor; Step (2), heating the metal complex precursor obtained in step (1) to the required temperature and then keeping it at that temperature for several hours, cooling it and taking it out to obtain a powder, that is, the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals.

6. The preparation method according to claim 5, characterized in that: The p-block metal and / or transition metal source is selected from: chlorides of p-block metals and / or transition metals, organic esters of p-block metals and / or transition metals, carbonyl compounds of p-block metals and / or transition metals, oxalates of p-block metals and / or transition metals, nitrates of p-block metals and / or transition metals, ammonium oxalates of p-block metals and / or transition metals, and low-valent or high-valent acid salts of p-block metals and / or transition metals; The ruthenium source is selected from: ruthenium chloride, ruthenium acetylacetonate, ruthenium carbonyl or ruthenium nitrosyl nitrate; The complex is a polymer containing multiple coordination points, selected from one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, polyethylene diamine, polylactic acid, polypyridine, citric acid, ethylenediaminetetraacetic acid and polyamide.

7. The preparation method according to claim 5, characterized in that: In the mixture in step (1), the concentration of the p-zone metal source and / or transition metal source is 0.01 to 1 mol / L; the concentration of the ruthenium source is 0.1 to 1 mol / L; the concentration of the complex is 1 to 40 g / L; and the molar ratio of ruthenium to all doping metals is 99:1 to 1:

1.

8. The preparation method according to claim 5, characterized in that: The heating rate in step (2) is 1-10°C / min, the required temperature is 400-600°C, and the insulation time is 3-6 hours.

9. Use of the ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals according to any one of claims 1 to 4 as an electrode material.

10. The use according to claim 9, characterized in that The ruthenium oxide nanomaterial doped with two or more p-zone metals and / or transition metals is used as an anode material for electrolyzing water to generate oxygen.